First-order and second-order ambiguity aversion - Matthias Lang (Max Planck Institute for Research on Collective Goods, 2015)
Different models of uncertainty aversion imply strikingly different economic behavior. The key to understanding these differences lies in the dichotomy between first-order and second-order ambiguity aversion which I define here. My definition and its characterization are independent of specific representations of decisions under uncertainty. I show that with second-order ambiguity aversion a positive exposure to ambiguity is optimal if and only if there is a subjective belief such that the acts expected outcome is positive. With first-order ambiguity aversion, zero exposure to ambiguity can be optimal. Examples in finance, insurance and contracting demonstrate the economic relevance of this dichotomy.
Keywords: D82; D01; D81; G11; 330; uncertainty aversion; ambiguity; smooth ambiguity aversion; sub-jective beliefs; kinked preferences